Experiencing inequality : ethnic minorities and the employment training scheme - Ogbonna, Emmanuel [Verfasser]; Noon, Mike [Verfasser] (My University, 1995)
"This article presents the results of an investigation into the participation and outcome rates of ethnic minorities on Employment Training (ET). It demonstrates that ethnic minorities are joining schemes in respresentative proportions, yet are not enjoying the positive outcomes experienced by their white counterparts. It presents qualitative data which uncovers the experiences of ethnic minority trainees and confirms that, whilst government training is perceiced as worthwhile, discrimination and prejudice distort the process to such an extent that inequality of opportunity occurs." (author's abstract, IAB-Doku) ((en)) Der Beitrag befasst sich mit der Beteiligung ethnischer Minderheiten an Trainingsmassnahmen für Arbeitslose in Grossbritannien. Es zeigt sich, dass ethnische Minderheiten zwar quantitativ ausreichend vertreten sind, qualitative Befragungsergebnisse verdeutlichen jedoch, dass die Trainingsmassnahmen für sie weniger erfolgreich verlaufen. (IAB)
Die Erfahrung von Ungleichheit : ethnische Minderheiten und Weiterbildungsmassnahmen für Arbeitslose
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; P 1.5 Migranten; I 2.2.1 Westeuropa; Arbeitsloser; Ethnische Gruppe; Berufliche Weiterbildung; Erfolgskontrolle; Diskriminierung; Teilnehmer; Einstellung; Quantitative Angaben; Großbritannien; 1992-1993